Characteristics of Listeria Monocytogenes Strains Persisting in a Meat Processing Facility over a 4-Year Period - Andrea Stoller; Marc J. A. Stevens; Roger Stephan; Claudia Guldimann (Pathogens, 2019)
Listeria monocytogenes can persist in food production facilities, resulting in serious threats to consumers due to the high mortality associated with listeriosis, especially in the very young, old and pregnant. We subtyped 124 strains of L. monocytogenes isolated from a meat processing facility in Switzerland by serotyping, multi locus sequence typing (MLST) typing and whole genome sequencing. We then analyzed their ability to form biofilms and their resistance to the disinfectants benzalkonium chloride (BC) and peracetic acid (PAA). The genotyping results of the strains showed that several clonal populations of L. monocytogenes belonging to CC9, CC204 and CC121 had persisted in this meat processing facility for at least four years. All of the strains showed biofilm forming capacity comparable to a known high biofilm forming strain. Known efflux pumps for BC were present in CC204, CC9 (brcABC) and CC121 (qacH) strains, while strains from other CC showed very low minimal inhibitory concentrations (MICs) for BC. For PAA, minimal bactericidal concentrations of 1.2–1.6% for 20 min and minimal inhibitory concentrations between 0.1 and 0.2% were observed. These values were close to or above the recommended concentration for use (0.5–1%), suggesting that PAA might be ineffective at controlling L. monocytogenes in this and potentially other meat processing facilities.